Resin composition for powder coating, powder coating, and article having coating film of said powder coating

The resin composition for powder coatings, featuring a specific blend of acrylic resin, vinyl monomer, and unsaturated monomers, addresses the challenges of smoothness, curability, rust resistance, and weather resistance, resulting in a high-performance coating film for diverse applications.

JP7653068B2Active Publication Date: 2025-03-28DIC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024530361
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-05-18
Publication Date
2025-03-28
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

Existing powder coatings face challenges in achieving a balance between smoothness, curability, rust resistance, and weather resistance, with previous formulations either compromising on smoothness or lacking sufficient weather resistance.

Method used

A resin composition for powder coatings is developed, comprising an acrylic resin with an epoxy group, a vinyl monomer with an aromatic ring, and other unsaturated monomers, with specific mass content ratios and preferred monomer compositions to enhance the properties of the cured coating film.

Benefits of technology

The proposed resin composition achieves a cured coating film with excellent smoothness, curability, rust resistance, and weather resistance, making it suitable for various applications including metal exteriors and home appliances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653068000001
    Figure 0007653068000001
  • Figure 0007653068000002
    Figure 0007653068000002
  • Figure 0007653068000003
    Figure 0007653068000003
Patent Text Reader

Abstract

Provided is a resin composition that is for a powder coating material and that comprises an acrylic resin (A) containing, as essential raw materials, an acrylic monomer (a1) having an epoxy group, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) other than said monomers (a1) and (a2). The resin composition for a powder coating material is characterized in that the chlorine atom content in the acrylic resin (A) is 100 mass ppm or less, and the contained amounts of the monomer (a1), the monomer (a2), and the monomer (a3) in monomer components which are the raw materials of the acrylic resin (A) are 10-50 mass%, 10-40 mass%, and 20-70 mass%, respectively. This resin composition for a powder coating material can form a cured coating film having exceptional smoothness, curability, filiform rust resistance, and weather resistance, and therefore can be used suitably in coating materials for coating a variety of articles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for powder coating, a powder coating, and an article having a coating film of the powder coating. [Background technology]

[0002] In recent years, regulations on organic solvents have become stricter due to problems such as air pollution, and environmentally friendly paints have been attracting attention. Among them, powder paints have been in the spotlight as solvent-free paints from the perspective of environmental protection, and acrylic powder paints in particular have been attracting attention for their use in automobile parts such as aluminum wheels, metal exteriors, and home appliances due to their excellent coating film performance such as weather resistance and stain resistance. However, powder paints have the disadvantage of being inferior in smoothness to solvent-based paints.

[0003] In response to this, a powder coating has been proposed that contains an epoxy group-containing acrylic resin obtained by copolymerizing an alkyl (meth)acrylate ester, an epoxy group-containing acrylic monomer, and other copolymerizable vinyl monomers, and a curing agent having a functional group capable of reacting with an epoxy group (see, for example, Patent Document 1). However, although the cured coating film obtained from this powder coating has improved smoothness, there is a problem in that it has insufficient weather resistance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-69368 A Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a resin composition for a powder coating, which is capable of giving a cured coating film excellent in smoothness, curability, filamentous rust resistance and weather resistance, a powder coating, and an article having a coating film of said coating. [Means for solving the problem]

[0006] As a result of intensive research by the present inventors to solve the above problems, they discovered that a cured coating film obtained from a resin composition for powder paint containing an acrylic resin whose essential raw materials are an acrylic monomer having an epoxy group, a vinyl monomer having an aromatic ring, and other monomers has excellent smoothness, curability, filamentous rust resistance, and weather resistance, and thus completed the present invention.

[0007] That is, the present invention relates to a resin composition for powder coating containing an acrylic resin (A) having as essential raw materials an acrylic monomer (a1) having an epoxy group, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) ​​other than the monomers (a1) and (a2), wherein the chlorine atom content in the acrylic resin (A) is 100 ppm by mass or less, and the monomer (a1) is 10 to 50 mass%, the monomer (a2) is 10 to 40 mass%, and the monomer (a3) ​​is 20 to 70 mass% in the monomer components that are raw materials for the acrylic resin (A), the powder coating, and an article coated with the coating. Effect of the Invention

[0008] The resin composition for powder coating of the present invention is capable of forming a cured coating film that is excellent in smoothness, curability, resistance to filamentous rust and weather resistance, and can therefore be suitably used in coatings for coating various articles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The resin composition for powder coating of the present invention is a resin composition for powder coating containing an acrylic resin (A) whose essential raw materials are an acrylic monomer (a1) having an epoxy group, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) ​​other than the monomers (a1) and (a2), wherein the chlorine atom content in the acrylic resin (A) is 100 ppm by mass or less, and the monomer (a1) is 10 to 50 mass%, the monomer (a2) is 10 to 40 mass%, and the monomer (a3) ​​is 20 to 70 mass% in the monomer components that are raw materials for the acrylic resin (A).

[0010] First, the acrylic resin (A) will be described. The acrylic resin (A) has an epoxy group and is obtained by copolymerizing the monomer (a1), the monomer (a2), and the monomer (a3).

[0011] By setting the chlorine atom content in the acrylic resin (A) to 100 ppm by mass or less, a coating film excellent in smoothness, curability, filamentous rust resistance and weather resistance can be obtained, and since weather resistance is further improved, the chlorine atom content in the acrylic resin (A) is preferably 50 ppm by mass or less, and more preferably 30 ppm by mass or less.

[0012] In the present invention, the chlorine atom content in the acrylic resin (A) is a value obtained by FP method using a fluorescent X-ray device.

[0013] The monomer (a1) is an acrylic monomer having an epoxy group, and examples thereof include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, (meth)allyl glycidyl ether, (meth)allyl methyl glycidyl ether, 3,4-epoxycyclohexylmethyl (meth)acrylate, etc., and glycidyl (meth)acrylate is preferred because it further improves smoothness, curability, and filament rust resistance. These monomers (a1) can be used alone or in combination of two or more kinds.

[0014] The monomer (a1) may contain chlorine compounds as impurities. Since the chlorine atom content in the acrylic resin (A) can be suppressed and the weather resistance can be easily improved, the chlorine atom content in the monomer (a1) is preferably 300 ppm by mass or less, more preferably 200 ppm by mass or less, and even more preferably 100 ppm by mass or less.

[0015] In the present invention, the chlorine atom content in the monomer (a1) is a value obtained by combustion ion chromatography.

[0016] From the viewpoint of sustainability, it is preferable to use, as the monomer (a1), one derived from a natural product.

[0017] In the present invention, "(meth)acrylic acid" refers to either or both of methacrylic acid and acrylic acid, "(meth)acrylate" refers to either or both of methacrylate and acrylate, "(meth)acrylamide" refers to either or both of methacrylamide and acrylamide, and "(meth)acryloyl group" refers to either or both of a methacryloyl group and an acryloyl group.

[0018] The monomer (a2) is a vinyl monomer having an aromatic ring, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, divinylbenzene, etc., among which styrene is preferred. These monomers (a3) ​​can be used alone or in combination of two or more kinds.

[0019] The monomer (a3) ​​is an unsaturated monomer other than the monomers (a1) and (a2), and examples thereof include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (Meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, Nt-butyl (meth)acrylamide, Nt-octyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, (Meth)acrylonitrile, N,N-dimethylaminoethyl (meth)acrylate, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 2-methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxy-n-butyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, monofunctional unsaturated monomers such as dimethyl-n-butyl (meth)acrylate, 3-hydroxy-n-butyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, glycerin mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, and lactone-modified (meth)acrylates having a hydroxyl group at the end;Ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, bisphenol A-di(meth)acryl Examples of the acrylic monomers include bifunctional unsaturated monomers such as bisphenol A-EO modified di(meth)acrylate, isocyanuric acid EO modified diacrylate, and the like; trifunctional or higher unsaturated monomers such as isocyanuric acid EO modified triacrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane EO modified tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol penta(meth)acrylate, and among these, alkyl(meth)acrylates having an alkyl group with 1 to 4 carbon atoms are preferred for the purpose of increasing the glass transition temperature of the cured coating film and improving the filament rust resistance. These acrylic monomers (a3) ​​can be used alone or in combination of two or more kinds.

[0020] The amount of the monomer (a1) used is 10 to 50 mass % in the monomer components that are the raw materials of the acrylic resin (A), and is preferably 10 to 40 mass % because this further improves the smoothness and curing properties of the coating film.

[0021] The amount of the monomer (a2) used is 10 to 40 mass% in the monomer components that are the raw materials of the acrylic resin (A), and is preferably 10 to 30 mass% because this further improves the smoothness, curing properties, filamentous rust resistance, and weather resistance of the coating film.

[0022] The amount of the monomer (a3) ​​used is 20 to 70 mass% in the monomer components that are the raw materials of the acrylic resin (A), and is preferably 40 to 70 mass% because this further improves the smoothness, curing properties, filamentous rust resistance, and weather resistance of the coating film.

[0023] The epoxy equivalent of the acrylic resin (A) is preferably from 250 to 1500 g / eq, more preferably from 350 to 1000 g / eq, since this further improves the smoothness, curability, filamentous rust resistance and weather resistance of the coating film.

[0024] The glass transition temperature of the acrylic resin (A) is preferably from 40 to 90°C, more preferably from 45 to 80°C, since this further improves the smoothness, curability, filamentous rust resistance and weather resistance of the coating film.

[0025] In the present invention, the glass transition temperature is FOX formula: 1 / Tg = W1 / Tg1 + W2 / Tg2 + ... (Tg: glass transition temperature to be determined, W1: weight fraction of component 1, Tg1: glass transition temperature of homopolymer of component 1) The glass transition temperature of the homopolymer of each component is determined by calculation according to the following formula: The glass transition temperature of the homopolymer of each component is determined by calculation according to the following formula:

[0026] Furthermore, the number average molecular weight of the acrylic resin (A) is preferably 1,000 to 10,000, more preferably 2,000 to 8,000, in order to provide excellent fluidity and resistance to filamentous rust when melted. Here, the number average molecular weight is a value calculated in terms of polystyrene based on gel permeation chromatography (hereinafter abbreviated as "GPC").

[0027] The acrylic resin (A) can be obtained by a known polymerization method using the monomers (a1) to (a3) ​​as raw materials, but a solution radical polymerization method is preferred because it is the simplest.

[0028] The above-mentioned solution radical polymerization method is a method in which each monomer, which is a raw material, is dissolved in a solvent and a polymerization reaction is carried out in the presence of a polymerization initiator. Examples of the solvent that can be used in this case include hydrocarbon solvents such as toluene, xylene, cyclohexane, n-hexane, and octane; alcohol solvents such as methanol, ethanol, isopropanol, n-butanol, isobutanol, and sec-butanol; ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and diethylene glycol dimethyl ether; ester solvents such as methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, and amyl acetate; and ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. These solvents can be used alone or in combination of two or more.

[0029] Examples of the polymerization initiator include ketone peroxide compounds such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, and 2,2-bis(4,4-ditert-butylperoxy)cyclohexane. peroxyketal compounds such as 2,2-bis(4,4-ditert-amylperoxycyclohexyl)propane, 2,2-bis(4,4-ditert-hexylperoxycyclohexyl)propane, 2,2-bis(4,4-ditert-octylperoxycyclohexyl)propane, and 2,2-bis(4,4-dicumylperoxycyclohexyl)propane; cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, peroxides; dialkyl peroxide compounds such as 1,3-bis(tert-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropylbenzene peroxide, and tert-butylcumyl peroxide; diacyl peroxide compounds such as decanoyl peroxide, lauroyl peroxide, benzoyl peroxide, and 2,4-dichlorobenzoyl peroxide; peroxycarbonate compounds such as bis(tert-butylcyclohexyl)peroxydicarbonate; and peroxyester compounds such as tert-butylperoxy-2-ethylhexanoate, tert-butylperoxybenzoate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; and azo compounds such as 2,2'-azobisisobutyronitrile and 1,1'-azobis(cyclohexane-1-carbonitrile).

[0030] The powder coating resin composition of the present invention contains the acrylic resin (A) described above, but it preferably contains a curing agent (B) having a functional group capable of reacting with an epoxy group, since this further improves the coating film properties.

[0031] The curing agent (B) is a curing agent having a functional group capable of reacting with an epoxy group, and examples thereof include polycarboxylic acid compounds such as suberic acid, azelaic acid, 2,4-diethylglutaric acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, brassylic acid, tetradecanedicarboxylic acid, pentadecanedicarboxylic acid, hexadecanedicarboxylic acid, heptadecanedicarboxylic acid, octadecanedicarboxylic acid, eicosanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and butanetricarboxylic acid, anhydrides of these polycarboxylic acids, and polyhydric phenol compounds. Among these, aliphatic polycarboxylic acid compounds and their anhydrides are preferred, and dodecanedicarboxylic acid is more preferred, since a high-strength coating film can be obtained. In addition, these curing agents (B) can be used alone or in combination of two or more kinds.

[0032] Regarding the blending amounts of the acrylic resin (A) and the curing agent (B) in the resin composition for powder coating of the present invention, since a coating film with high strength can be obtained, the equivalent ratio (A / B) of the equivalent number of epoxy groups in the acrylic resin (A) to the equivalent number of functional groups capable of reacting with epoxy groups in the curing agent (B) is preferably 0.5 to 1.5, more preferably 0.8 to 1.2.

[0033] To the resin composition for powder coating of the present invention, various known and commonly used additives such as organic or inorganic pigments, leveling agents, flow control agents, antifoaming agents, light stabilizers, ultraviolet absorbers, antioxidants, etc. can be added within the range that does not impair the effects of the present invention. A catalyst can also be added for the purpose of promoting the curing reaction during baking.

[0034] In order to improve the filament rust resistance of the coating film, the resin composition for powder coating of the present invention may further contain silica and hydrolyzable silane compounds such as alkoxysilanes and silane coupling agents within the range that does not impair the effects of the present invention. These compounds may be used alone or in combination of two or more kinds.

[0035] Examples of suitable silane coupling agents include glycidylalkoxysilane and aminoalkoxysilane, etc. Among these, glycidyltrialkoxysilane is preferred because it provides a coating film with excellent filamentary rust resistance, and glycidyltrimethoxysilane is more preferred.

[0036] The amount of the silane coupling agent blended in the resin composition for powder coating is preferably 0.01 to 3 mass %, and more preferably 0.01 to 1 mass %, since a coating film excellent in filamentary rust resistance can be obtained.

[0037] The powder coating of the present invention can be prepared by various known and commonly used methods. For example, the acrylic resin (A), the curing agent (B), and, if necessary, various additives such as pigments and surface conditioners are mixed, and then the mixture is melt-kneaded, followed by fine pulverization and classification, in other words, a mechanical pulverization method.

[0038] The powder coating material of the present invention can be applied to exteriors, home appliances, automobile products, motorcycle products, protective fences, and the like, but since it gives a coating film with excellent appearance and excellent smoothness, curing properties, resistance to thread rust, and weather resistance, it is also suitable for application to metal components such as aluminum wheel alloy components.

[0039] The method of applying the powder coating of the present invention includes various known and commonly used methods such as electrostatic powder coating. The method of forming a cured coating film after applying the powder coating of the present invention can be appropriately selected depending on the type of substrate and the purpose, but it is preferable to bake the coating film at a temperature range of 120 to 250°C for 5 to 30 minutes, since this produces a coating film with excellent filiform rust resistance, water resistance, and weather resistance. The coating film thickness is preferably in the range of 50 to 200 μm. EXAMPLES

[0040] The present invention will be described in more detail below with reference to specific examples. The chlorine atom content in the monomer, the chlorine atom content in the acrylic resin, the epoxy equivalent and the number average molecular weight of the acrylic resin were measured by the following methods.

[0041] [Method for measuring the content of chlorine atoms in monomers] The chlorine atom content was measured by combustion ion chromatography using an automatic combustion apparatus (Mitsubishi Chemical Analytech's "AQF-2100H") and an ion chromatograph (Thermo Fisher Scientific's "ICS-6000")

[0042] [Method for measuring the chlorine atom content in acrylic resin] The chlorine atom content was measured by the FP method using an X-ray fluorescence spectrometer (Rigaku's "ZSX Primus"). The measurement conditions for the X-ray fluorescence spectrometer were as follows: X-ray source: Rh tube Output: 30kV, 30mA Measurement diameter: 30mm

[0043] [Method for measuring epoxy equivalent] Measured by hydrochloric acid-pyridine method. 25 ml of hydrochloric acid-pyridine solution was added to the resin, and it was dissolved by heating at 130℃ for 1 hour. Then, it was titrated with 0.1N potassium hydroxide alcohol solution using phenolphthalein as an indicator. The epoxy equivalent was calculated from the amount of 0.1N potassium hydroxide alcohol solution consumed.

[0044] [Method for measuring number average molecular weight] Measured by GPC. Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 4 mg / mL in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following monodisperse polystyrene.

[0045] (monodisperse polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0046] (Preparation of Glycidyl Methacrylate) Chlorine-free glycidyl methacrylate (NOF Corporation, "Blenmer GS") and normal glycidyl methacrylate (Mitsubishi Gas Chemical Company, Inc., "GMA (glycidyl methacrylate)") were mixed to obtain glycidyl methacrylates (hereinafter abbreviated as "GMA") with different chlorine atom contents, GMA (1) to (5).

[0047] The chlorine atom contents in the GMA (1) to (5) prepared above are shown in Table 1.

[0048] [Table 1]

[0049] (Synthesis Example 1: Synthesis of acrylic resin (A-1)) A reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet was charged with 67 parts by mass of xylene and heated to 135°C under a nitrogen atmosphere. A mixture consisting of 30 parts by mass of styrene (hereinafter abbreviated as "St"), 30 parts by mass of methyl methacrylate (hereinafter abbreviated as "MMA"), 40 parts by mass of GMA (1), and 6.0 parts by mass of t-butylperoxy 2-ethylhexanoate was added dropwise to the reaction vessel over a period of 6 hours, and the mixture was maintained at the same temperature for 6 hours after the end of the addition to carry out a polymerization reaction. Thereafter, the solvent was removed under a reduced pressure of 20 mmHg at 160°C to obtain a solid acrylic resin (A-1) having a number average molecular weight of 3,000, a glass transition temperature of 78°C, and an epoxy equivalent of 360 g / eq.

[0050] (Synthesis Example 2: Synthesis of acrylic resin (A-2)) A solid acrylic resin (A-2) having a number average molecular weight of 3,000, a glass transition temperature of 68°C, and an epoxy equivalent of 570 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 20 parts by mass of St, 35 parts by mass of MMA, 20 parts by mass of butyl methacrylate (hereinafter, abbreviated as "BMA"), and 25 parts by mass of GMA (2).

[0051] (Synthesis Example 3: Synthesis of acrylic resin (A-3)) A solid acrylic resin (A-3) having a number average molecular weight of 3,000, a glass transition temperature of 69°C, and an epoxy equivalent of 570 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 10 parts by mass of St, 45 parts by mass of MMA, 20 parts by mass of BMA, and 25 parts by mass of GMA (3).

[0052] (Synthesis Example 4: Synthesis of acrylic resin (A-4)) A solid acrylic resin (A-4) having a number average molecular weight of 3,000, a glass transition temperature of 49°C, and an epoxy equivalent of 950 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 20 parts by mass of St, 15 parts by mass of MMA, 50 parts by mass of BMA, and 15 parts by mass of GMA (4).

[0053] (Synthesis Example 5: Synthesis of acrylic resin (RA-1)) A solid acrylic resin (RA-1) having a number average molecular weight of 3,000, a glass transition temperature of 78°C, and an epoxy equivalent of 360 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 30 parts by mass of St, 30 parts by mass of MMA, and 40 parts by mass of GMA (5).

[0054] The monomer compositions of the acrylic resins (A-1) to (A-4) and (RA-1) synthesized in Synthesis Examples 1 to 4 above are shown in Table 2.

[0055] [Table 2]

[0056] (Example 1: Production and evaluation of powder coating (1)) A resin composition containing 85.0 parts by mass of the acrylic resin (A-1) obtained in Synthesis Example 1, 15.0 parts by mass of dodecanedicarboxylic acid (hereinafter abbreviated as "DDDA"), 0.5 parts by mass of benzoin, and 0.3 parts by mass of a leveling agent (ESTRON's "Resiflow LF") was melt-kneaded using a twin-screw kneader (Tsubako Yokohama Sales Co., Ltd.'s "APV Kneader MP-2015 Model"), then finely pulverized and further classified using a 200-mesh wire screen to obtain powder coating (1).

[0057] [Preparation of cured coating film for evaluation] The powder coating material obtained above was electrostatically powder coated onto an untreated aluminum plate (A-1050P) (7 cm x 15 cm) so that the film thickness after baking would be 80 to 120 μm, and then baked at 170°C for 20 minutes to produce a cured coating film for evaluation.

[0058] [Evaluation of smoothness] The cured coating film for evaluation obtained above was judged using standard plates for visually judging the smoothness of powder coating films by PCI (Powder Coating Institute). There are 10 standard plates, ranging from 1 to 10, with the larger the number, the better the smoothness. The smoothness of the powder coating film produced was judged by visual inspection to see which standard plate the smoothness corresponded to, and the smoothness was evaluated.

[0059] [Evaluation of hardening] 0.5 g of the powder coating material obtained above was dropped onto a hot plate heated to 160° C., and the time until the tack disappeared (gel time) was measured. Based on the gel time, the curability was evaluated as follows. ○: Gel time is less than 160 seconds △: Gel time is 160 seconds or more and less than 200 seconds ×: Gel time is 200 seconds or more

[0060] [Evaluation of thread rust resistance] The cured coating film obtained above was cut with a cutter knife into two straight lines of 13 cm each so that they reached the base material of the substrate, and the following test was performed using a CASS tester. Test 1 involved spraying saltwater (prepared by dissolving 2.6 g of copper (II) chloride hydrate, 10 cc of glacial acetic acid, and 500 g of ordinary salt in 10 L of ion-exchanged water) for 6 hours under conditions of temperature 50°C, spray volume 1.2-1.8 cc / h, and spray pressure 0.1 MPa, and test 2 involved leaving the film for 96 hours under conditions of temperature 60°C and humidity 85%, for a total of 5 cycles. After the CASS test was completed, the filamentous rust that had developed from the scratches on the coated plate was visually confirmed, and the filamentous rust resistance of the coating film was judged based on the length of the longest filamentous rust that had grown, as follows: ○: The longest length of the rust thread is 2.0 mm or less △: The longest length of the rust thread is more than 2.0 mm and less than 3.0 mm ×: The longest length of the rust thread exceeds 3.0 mm.

[0061] [Weather resistance evaluation] The cured coating film for evaluation obtained above was measured using a Super Xenon Weather Meter SX75 (manufactured by Suga Test Instruments Co., Ltd., light source: xenon arc lamp (water-cooled 7.5 kW), irradiance: 180 W / m 2After 1,800 hours of exposure under the following conditions: irradiation conditions: 60±3°C, 50±5% RH, irradiation and rain conditions: 38±3°C, irradiation / irradiation and rain cycle = 102 minutes / 18 minutes), the specular reflectance (gloss value) (%) of the coating film was evaluated as the retention rate (gloss retention rate: %) of the specular reflectance (gloss value) of the cured coating film before exposure [(100 x specular reflectance of coating film after exposure) / (specular reflectance of cured coating film before exposure)]. A higher retention rate indicates better weather resistance. Specular reflectance was measured using Micro Trigloss manufactured by BYK Corporation. 〇: Gloss retention rate 80% or more △: Gloss retention rate is 70% or more but less than 80% ×: Gloss retention rate less than 70%

[0062] (Examples 2 to 4: Production and evaluation of powder coating materials (2) to (4)) Powder coating materials (2) to (4) were prepared in the same manner as in Example 1, except that the acrylic resin (A-1) used in Example 1 was changed to acrylic resins (A-2) to (A-4), and various physical properties were evaluated.

[0063] (Comparative Example 1: Production and Evaluation of Powder Coating (R1)) A powder coating (R1) was prepared in the same manner as in Example 1, except that the acrylic resin (A-1) used in Example 1 was changed to an acrylic resin (RA-1), and various physical properties were evaluated.

[0064] Table 3 shows the blend compositions and evaluation results of the powder coating materials (1) to (4) obtained in the above Examples 1 to 4 and the powder coating material (R1) obtained in Comparative Example 1.

[0065] [Table 3]

[0066] It was confirmed that the cured coating films obtained from the resin compositions for powder coatings of the present invention in Examples 1 to 4 were excellent in smoothness, curability, filamentous rust resistance, and weather resistance.

[0067] On the other hand, Comparative Example 1 is an example in which the chlorine atom content in the acrylic resin exceeds 100 ppm by mass, which is the upper limit of the present invention, and it was confirmed that the weather resistance of the coating film was insufficient.

Claims

1. A powder coating material for aluminum wheel alloy members obtained from a resin composition for powder coating containing an acrylic resin (A) whose essential raw materials are an acrylic monomer (a1) having an epoxy group, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) ​​other than the monomers (a1) and (a2), wherein the chlorine atom content in the acrylic resin (A) is 100 ppm by mass or less, and the monomer (a1) is 10 to 50 mass%, the monomer (a2) is 10 to 40 mass%, and the monomer (a3) ​​is 20 to 70 mass% in the monomer components that are the raw materials for the acrylic resin (A).

2. 2. The powder coating material for alloy members of aluminum wheels according to claim 1, wherein the chlorine atom content in the monomer (a1) is 300 ppm by mass or less.

3. 2. The powder coating material for alloy members of an aluminum wheel according to claim 1, further comprising a curing agent (B) having a functional group capable of reacting with an epoxy group.

4. An aluminum wheel alloy member having a coating film of the powder paint for aluminum wheel alloy members according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Epoxy resin for decorative powder coating

    JP1986097373A

  • Modified resin powder

    JP2000053820A

  • Soldering resist ink

    JP2001324801A

  • powder transparent paint

    JP2001517724A

  • Thermosetting powder coating composition for aluminum wheel alloy member and aluminum alloy wheel member

    JP2002069368A